Editorial (Ultrasound International Open, 2016)
It is my honor to announce that the fourth issue of UIO has been published and is now available online.We are very happy that UIO was just accepted for inclusion in PubMed Central (PMC). This is a great achievement by the Editorial Board, the reviewers and, of course, the authors.